Dynamics of Overlapping Clusters: Industrial and Institutional Revolution in the Industrial District of Aachen, 1800‐1860 - Reckendrees, Alfred (Revista de Historia Industrial, 2017)
The economic transition characterizing the process of European industrialisation in the 19th century was concentrated on regions rather than on states. In the first half of the 19th century, the region of Aachen (in the west of Prussia) pioneered this development in the territory of the German states and became a powerful industrial region. The implementation and diffusion of the factory system and the economic impact of adapted and new institutions make up the core of this paper. Reciprocal interconnections between firms of different clusters shaped the region and created economic dynamics. Investments transgressed the boundaries of single industries and new industries emerged. One important feature of the regional production system was cross-sectional knowledge transfer; a second was institutions supportive to this process.